THE EFFECT OF ANAGRAM GAME ON STUDENTS’ VOCABULARY ACHIEVEMENT AT GRADE EIGHT OF SMP NEGERI 8 PEMATANGSIANTAR - Heppy Sinaga; Herman Herman; Eben Pasaribu (STKIP Persada Khatulistiwa Sintang, 2020)
This research is aimed to find out whether using Anagram Game give significant effect on students’ vocabulary achievement at grade eight of SMP Negeri 8 Pematangsiantar. Problem raised in this research is “What is the effect of Anagram Game on students’ vocabulary achievement at grade eight of SMP Negeri8 Pematangsiantar?”. To answer this problem the researcher uses some theories, namely: Bachtiar (2014), Harmer (2002), Hiebert and Kamil (2005), Hatch and Farhady (1982) and Sutherland (2009). This research is quantitative research design. Experimental was conducted as the method. The sample of this research are two classes which are VIII-4 as a control class because they are active with better achievement than other class and VIII-9 as an experimental class because they have lower achievement. The result shows that using Anagram Game on students’ vocabulary achievement at grade eight of SMP Negeri 8 Pematangsiantar got high level where as the score of t-test (4.65) was higher than t-table (1.679) at level of significant 5% for two tailed test. So Null Hypothesis was rejected and Alternative Hypothesis was accepted. After analyzing the data, the researcher concludes that using Anagram Game significantly affect the students’ vocabulary achievement and her suggestion is English teacher should have creative method in teaching English to their students especially to increase their vocabulary by using Anagram Game, so that they are not boring to learn English and make the enjoy on it.